Phage therapy combined with Gum Karaya injectable hydrogels for treatment of methicillin-resistant Staphylococcus aureus deep wound infection in a porcine model - Vacek, L; Polaštík Kleknerová, D; Lipový, B; Holoubek, J; Matysková, D; Černá, E; Brtníková, J; Jeklová, E; Kobzová, Š; Janda, L; Lišková, L; Diabelko, D; et al. (International journal of pharmaceutics, 2024)
Skin and soft tissue infections (SSTIs) represent a significant healthcare challenge, particularly in the context of increasing antibiotic resistance. This study investigates the efficacy of a novel therapeutic approach combining bacteriophage (phage) therapy with a gum Karaya (GK)-based hydrogel delivery system in a porcine model of deep staphylococcal SSTIs. The study exploits the lytic activity and safety of the Staphylococcus phage 812K1/420 of the Kayvirus genus, which is active against methicillin-resistant Staphylococcus aureus (MRSA). The GK injectable hydrogels and hydrogel films, developed by our research group, serve as effective, non-toxic, and easy-to-apply delivery systems, supporting moist wound healing and re-epithelialization. In the porcine model, the combined treatment showed asynergistic effect, leading to a significant reduction in bacterial load (2.5 log CFU/gram of tissue) within one week. Local signs of inflammation were significantly reduced by day 8, with clear evidence of re-epithelialization and wound contraction. Importantly, no adverse effects of the GK-based delivery system were observed throughout the study. The results highlight the potential of this innovative therapeutic approach to effectively treat deep staphylococcal SSTIs, providing a promising avenue for further research and clinical application in the field of infections caused by antibiotic-resistant bacteria.
Keywords: Methicillin-Resistant Staphylococcus aureus; Disease Models, Animal; Wound Healing; zvířata; methicilin rezistentní Staphylococcus aureus; prasata; Wound Infection; fágová terapie; Animals; rostlinné gumy; modely nemocí na zvířatech; Phage Therapy; infekce v ráně; Staphylococcal Infections; Female; Staphylococcus Phages; ženské pohlaví; hojení ran; Hydrogels; stafylokokové bakteriofágy; Swine; stafylokokové infekce; Plant Gums; hydrogely